Self Efficacy dan Self Motivation Kader dalam Melakukan Active Case Finding untuk Menurunkan Epidemi Tuberculosis dalam Mewujudkan Target SDGs 2030 - Lenci Aryani; Sri Handayani (VISIKES: Jurnal Kesehatan Masyarakat, 2017)
Active case inding maximize the role of cadres for the discovery of new TB cases. Semarang city emergency TB in 2016. Puskesmas Mijen one who has high TB patients with case notiication number of 53%. This research is observational research with cross sectional method. This study uses questionnaires as a tool in taking data. The ield samples were chosen by simple random. The sample size is 55 cadres in the working area of Mijen Semarang Public Health Center. The results of the good category of 36,4% self eicacy conident cadre performancein TB case inding in the community at least once a day. There are 38,2% self motivation of additional income knowledge of cadres including less in the case inding of Tb in the working environment of the Mijen Puskesmas. Self eicacy factors and self-motivation of cadre showed no signiicant relationship with cadre performance on the implementation process at family visit to get target of SDGS 2030. It is suggested to all health center cadres to always follow training on health especially related to TB to maximize the role of cadre for discovery New TB caseKeywords: Self eicay, self motivation, tuberculosis